Mike & Riel Mystery: Dead Silence - Book 5 - McClintock, Norah (Minneapolis : Darby Creek, 2014)
Mike's friend has been murdered and he is determined to find out who did it.
Keywords: Mystery and detective stories; Murder -- Fiction; Foster home care -- Fiction